From Bill Shankly to the Huffington Post: How to Increase Critical Thinking in Experimental Psychology Course? - Lacot, Emilie; Blondelle, Geoffrey; Hainselin, Mathieu (Frontiers in Psychology, 2016)
Although critical thinking and source checking are basic prerequisites to become a psychologist, or a scientist, it is usually difficult to have students interested in experimental methods courses. Most first year students are tempted not to attend these courses. Such behaviors are reinforced by arguments that “everybody is different” and “people are not numbers”. Consequently, students have difficulties to develop source and evidence checking skills, and may be more prone to believe in any supposed expert. This paper presents two ways to involve students during lectures and seminars. The first method consists in presenting, during the initial lecture of the year, a fake scientific concept which students will believe as true. This phenomenon is called the “Bill Shankly syndrome” and it only exists if someone believes that the information is given by a serious lecturer, presenting oneself as a world-class researcher. The second method consists in training students to become reviewers using evidence checking of a mainstream media article which promises scientifically proven ways to be happy. The use of these methods may stimulate students’ interest in research methods and its practical applications from week one.